THE STUDY OF ECONOMIC FEASIBILITY OF WATERMELON FARMING IN CENTRAL LOMBOK REGENCY - Aeko Fria Utama FR; Dudi Septiadi (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2023)
This study aims to analyze the income and economic feasibility of watermelon farming in Central Lombok Regency. Watermelon is one of the agricultural commodities that has a promising economic potential in the area. Analysis of income and economic feasibility is a key factor in determining the success of farming and development of the agricultural sector. The research method used was a direct survey of watermelon farmers in West Praya District, Central Lombok Regency. Primary data on production costs, selling prices, production volumes, and other factors affecting the income of watermelon farming were collected and analyzed descriptively. It was determined that 30 respondents came from the 4 highest watermelon-producing villages in the region. Then the proportions of the four villages are proportional sampling. The results of this study indicate that watermelon farming in the research location has a fairly high income potential. Based on the value of the R/C ratio, watermelon farming is categorized as a feasible or profitable farming business. The level of profitability of watermelon farming in the study area is high or the profit level is high. The main constraints faced by the respondent farmers include, among others, constraints with erratic weather and pest and disease attacks